PCT, IL-6, and IL-10 facilitate early diagnosis and pathogen classifications in bloodstream infection - Xianggui Yang; Jun Zeng; Xuejing Yu; Zhenguo Wang; Dan Wang; Qin Zhou; Tingting Bai; Ying Xu (BMC, 2023)
Abstract Background In the diagnosis of bloodstream infection (BSI), various inflammatory markers such as C-reactive protein (CRP), procalcitonin (PCT), interleukins (IL), white blood cell count (WBC), neutrophil percentage (NE%), platelet count (PLT), and erythrocyte sedimentation rate (ESR) have been extensively utilized. However, their specific roles in distinguishing BSI from local bacterial infection (LBI) and in classifying BSI pathogens remain uncertain. Methods A historical cohort study was conducted, involving the enrollment of 505 patients with BSI and 102 patients with LBI. To validate the reliability of the clinical data obtained from this cohort, mouse models of BSI were utilized. Results Our findings revealed that patients with BSI had significantly higher levels of inflammatory markers, including CRP, PCT, IL-6, IL-10, WBC, NE%, and ESR, compared to those with LBI (p < 0.05). The receiver operating characteristic (ROC) curve analysis demonstrated that CRP, PCT, IL-6, IL-10, ESR and NE% exhibited excellent diagnostic efficacy for BSI. Additionally, we observed significant differences in CRP, PCT, IL-6, and IL-10 levels between patients with BSI caused by Gram-positive bacteria (GP-BSI) and Gram-negative bacteria (GN-BSI), but no significant variations were found among specific bacterial species. Furthermore, our study also found that CRP, PCT, and IL-10 have good discriminatory ability for vancomycin-resistant Enterococcus (VRE), but they show no significant diagnostic efficacy for other multidrug-resistant organisms (MDROs) such as carbapenem-resistant Enterobacteriaceae (CRE), carbapenem-resistant Pseudomonas aeruginosa (CRPA), and methicillin-resistant Staphylococcus aureus (MRSA). In our mouse model experiments, we observed a remarkable increase in PCT, IL-6, and IL-10 levels in mice with GN-BSI compared to those with GP-BSI. Conclusion Our study has confirmed that PCT, IL-6, and IL-10 are efficient biomarkers for distinguishing between BSI and LBI. Furthermore, they can be utilized to classify BSI pathogens and differentiate between VRE and vancomycin-susceptible Enterococcus. These findings are extremely valuable for clinicians as they enable timely initiation of empiric antibiotic therapies and ultimately lead to improved clinical outcomes for patients with BSI.